Hubungan Kandungan N-Total Dan C-Organik Tanah Terhadap Berat Panen Tanaman Pakcoy Setelah Dikombinasikan Dengan Kompos Sampah Kota Dan Pupuk Kandang Sapi Pada Aluvial, Indramayu - Henly Yulina; Wiwik Ambarsari (Jurnal Agro Wiralodra, 2021)
The objective of this research was to find out relationship between N- Total content and C- Organic soil to the harvest weight of pakcoy after combined with municipal waste compost and cow manure in Alluvial, Indramayu. This study used a randomized block design factorial with two factors. The first factor is municipal waste compost and the second factor is cow manure. Each of them consisted of 4 levels : 0%, 3.0%, 6.0%, and 9.0% with two replication, followed by regression analysis and linear correlation. The results showed that there was a relationship between N- Total content and C- Organic soil with harvest weight of pakcoy. The harvest weight of pakcoy was influenced by N- Total content and C-Organik soil, so that the N- Total and C-Organic soil can increase the harvest weight of pakcoy.